2000
DOI: 10.1034/j.1399-3003.2000.15.10.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgement of airway inflammation versus sputum cell counts in patients with asthma

Abstract: The inflammatory component of asthma is usually assessed indirectly by symptoms and spirometry, these may be inaccurate. It can now be assessed directly and reliably by the examination of sputum cell counts. There is no information on how clinical assessment of the presence and type of airway inflammation compares with actual measurements.In this single-centre observational study, sputum was collected from 76 consecutive adults with asthma attending a tertiary chest clinic after their physicians had recorded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 31 publications
2
40
0
3
Order By: Relevance
“…However, assessing the underlying eosinophilic airway inflammation may add an extra feature to asthma management [31]. In our study, more than half of the patients had at least one blood eosinophil count whereas less than 10% of the patients had a sputum eosinophil count.…”
Section: Discussionmentioning
confidence: 74%
“…However, assessing the underlying eosinophilic airway inflammation may add an extra feature to asthma management [31]. In our study, more than half of the patients had at least one blood eosinophil count whereas less than 10% of the patients had a sputum eosinophil count.…”
Section: Discussionmentioning
confidence: 74%
“…Sputum eosinophils are more responsive to change, increasing ahead of clinical variables [21] and exhaled NO during exacerbations [22], and respond more slowly to treatment [23]. It would therefore not be surprising if clinicians were poor at judging whether airway inflammatory was present surprising or not [24].…”
Section: Rationale For Sputum Examinationmentioning
confidence: 99%
“…However, like other measurements, it would not be surprising if physicians were not good at recognizing the presence or type of inflammatory cell infiltration [24]. The authors have found sputum cell counts to be useful in assessing and managing difficult asthma ( fig.…”
Section: How To Use Sputum Examination In Clinical Practicementioning
confidence: 99%
“…Moreover, asthma symptoms correlate poorly with abnormalities of lung function 9 and airway inflammation, 10,11 and thus in isolation may suggest a less severe form of the disease than is actually present. Although many clinicians diagnose asthma on the basis of a trial of therapy, objective measurements are necessary to confirm the clinical diagnosis.…”
Section: The Casementioning
confidence: 99%